التأطير الإعلامي لقضايا تسيير سياسات القطاع الصحي الجزائري في النشرات الإخبارية التلفزيونية - زياد إسماعيل (University of Eloued جامعة الوادي, 2024)
تعالج هذه المداخلة الأطر الإعلامية التي اعتمدت عليها النشرات الإخبارية التلفزيونية لمختلف القنوات الجزائرية العامة والخاصة في معالجة أهم قضايا تسيير سياسات القطاع الصحي في الجزائر، معتمدين في ذلك على المنهج المسحي والمقارن، استمارة تحليل المضمون كأداة لجمع البيانات، وعلى عينة قصدية من النشرات الإخبارية التلفزيونية، وعلى نظرية الإطار الإعلامي. Abstract: This intervention addresses the media frameworks on which the television news bulletins of various public and private Algerian channels relied to address the most important issues in the management of health sector policies in Algeria, relying in this on the survey and comparative method, the content analysis form as a tool for collecting data, and on a purposive sample of television news bulletins, And on the theory of media frame
دراسة تحليلية لعينة من النشرات الإخبارية
Keywords: التأطير الإعلامي; قضايا تسيير سياسات القطاع الصحي الجزائري; Media framing; issues of policy management in the Algerian health sector; television news bulletins; an analytical study